Effect of Addition of Different Levels of Commercial Baker's Yeast to Concentrate Diet of Multiparous Mid-Lactation Holstein Friesian Cows on Rumen Fermentation Characteristics (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was conducted in Grand station of Diwania/ Taj Al-Nahrain company- Al-Qadisiya Province for 84 days to investigate the effect of level of addition of commercial baker's yeast Saccharomyces cerevisiae,0, 15 and 30 g/cow/day to concentrate diet on rumen fermentation characteristics  in German Holstein Friesian lactating cows.  Nine multiparous Holstein cows in their mid-lactation were used. Daily feeding program applied in that station included offering 1 kg of concentrate diet per 3-4 kg milk produced divided into morning and evening meals, 10 kg of green forage, 10 kg whole plant corn silage and free choice of rice straw. Silage was characterized with accepted quality and fermentation parameters, values of pH, concentrations of ammonia nitrogen (NH3-N) and total volatile fatty acids (TVFA) were, 3.5, 0.98% of total nitrogen and 2.55 mM/DM respectively. Results revealed that addition of yeast at level of 15 and 30 g/cow/day reduced (P